KUALITAS TIDUR BERHUBUNGAN DENGAN BOURNOUT (KELELAHAN) PADA PEKERJA DEWASA - Putri, Ronasari Mahaji; Devi, Hilda Mazarina (Dian Nuswantoro Semarang, 2024)
The high buornout among adult workers has an impact on decreasing work productivity. Sleep quality as one of the factors thought to affect bournout. The aim of the study was to determine the relationship between sleep quality and bournout in middle-adult workers. The research design used cross-sectional. A sample of 42 people was obtained by purposive sampling technique. The variable in this study is quality with the dependent variable being bournout. The sleep quality instrument uses the Pittsburgh Sleep Quality Index (PSQI), while bournout uses a questionnaire. Data was collected by distributing questionnaires packaged in the form of a google form. Data analysis used the Spearman rank test with the help of SPSS version 18 software. The results showed that most of the respondents had quite poor sleep quality (78.6%); most respondents have bournout levels in the medium and high categories, which are 45.2% each; there is a relationship between sleep quality and bournout (p-value 0.039). It is recommended to examine the Health Belief Model (HBM) bournout analysis in middle-aged workers.